2021
DOI: 10.1097/md.0000000000024628
|View full text |Cite
|
Sign up to set email alerts
|

Burst spinal cord stimulation for central neuropathic pain

Abstract: Introduction: Central neuropathic pain can result from any type of injury to the central nervous system. Treatment of central neuropathic pain is very challenging. Recently, a novel stimulation paradigm, called burst stimulation, has been presented as an excellent alternative in a group of patients with intractable central neuropathic pain. We report 2 cases where burst spinal cord stimulation (SCS) was applied in patients with neuropathic pain due to spinal cord injury (SCI) or traumatic brain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…She experienced both reduction in pain frequency and intensity after B-SCS, with effects lasting at 3-month follow up. B-SCS was also utilized in a 52-year old male diagnosed with at-level SCI neuropathic pain having a T12 neurological level of injury with pain localizing to his right anterolateral thigh ( 60 ). Pain intensity and frequency were found to be reduced by half with undiminished efficacy of stimulation at 1-year follow up.…”
Section: Modalitiesmentioning
confidence: 99%
“…She experienced both reduction in pain frequency and intensity after B-SCS, with effects lasting at 3-month follow up. B-SCS was also utilized in a 52-year old male diagnosed with at-level SCI neuropathic pain having a T12 neurological level of injury with pain localizing to his right anterolateral thigh ( 60 ). Pain intensity and frequency were found to be reduced by half with undiminished efficacy of stimulation at 1-year follow up.…”
Section: Modalitiesmentioning
confidence: 99%
“…Recently, a novel mode of stimulation has been proposed as an excellent alternative for the treatment of persistent central nervous pain, namely, sudden stimulation. Yoon and Kim 80 used burst SCS and found that the efficacy of burst SCS in central neuropathological pain is desirable. We all know that new advancements in SCS treatment can provide effective pain relief in patients with chronic pain.…”
Section: Technological Advances In Scsmentioning
confidence: 99%